Religion and Contemporary Ecology: Laudato Si and Ibn Arabi's Eco-Spirituality in the Perspective of Open Integrity - Mochamad Ziaul Haq; Benedict Erick Mutis; Gerardette Philips (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the relationship between religious teachings and ecological awareness in responding to the environmental crisis in Indonesia. Specifically, the study focuses on Islam and Catholicism, examining the thoughts of Ibn Arabi and the concept of ecospirituality in Laudato Si. This research arises from the phenomenon of natural resource exploitation and the involvement of religious organizations in the management of mining areas. It questions the role of religion in limiting destructive behavior toward the environment. The study uses a qualitative method with data collection techniques through literature review on ecology, religion, and environmental policies. The findings reveal that the ecospirituality of Islam (Ibn Arabi) and Catholicism (Laudato Si) promote a triadic relationship: human, nature, and God. Human actions impact the understanding of nature and divinity. The process of humans honoring nature is akin to honoring the love and blessings of life from God. Nature can be seen as a mother who nurtures and cares for her children (humankind). Religion plays a key role here, particularly through its categorical imperatives. For example, the concept of ‘Insan Kamil,’ emphasized continuously by Muslims, or the ecospiritual encyclical Laudato Si, which stimulates ecological awareness in contemporary humans. This study offers a new interdisciplinary contribution to understanding the ecological crisis, especially in Indonesia, by integrating the religious dimension as a potential solution for environmental sustainability.